Nasopharyngeal colonisation with Streptococcus pneumoniae in malnourished children: a systematic review and meta-analysis of prevalence. (9th January 2019) - Smith, Holly C; German, Esther; Ferreira, Daniela M; Rylance, Jamie
Abstract: Background: Streptococcus pneumoniae is an intermittent commensal organism in the nasopharynx. Colonisation is a prerequisite for disease and malnourished children are especially susceptible to severe infection. This systematic review examines published prevalence rates of pneumococcal colonisation in the upper respiratory tract of chronically malnourished children <5 y of age. Methods: A systematic literature search was performed using MEDLINE, PubMed, Web of Science and Scopus. After screening, relevant studies were assessed for quality using Strengthening the Reporting of Observational Studies in Epidemiology criteria. Colonisation data were extracted and a random effects model was used to pool prevalence estimates. Results: Nine studies were included. The prevalence rate of S. pneumoniae colonisation in malnourished children during the first month of life ranged from 1.0 to 2.0%, increasing at 2 mo to 53.9–80.0%. Carriage remained similar from 3 to 60 mo at 64.1–88.0%. Meta-analysis showed a pooled prevalence of 67.2% in infants 0–3 mo of age (95% confidence interval [CI] 55.6 to 78.7), 77.9% in infants 3–6 mo of age (95% CI 68.1 to 87.7) and 77.8% in infants 6–60 mo of age (95% CI 73.9–81.6%). Conclusions: In malnourished children, it is plausible that rates of pneumococcal colonisation are higher than in healthy, well-nourished children. Knowledge of colonisation rates can inform policies on vaccination and ancillary interventions during treatment of malnutrition. Future studies should assess the impact of reducing colonisation on disease rates or transmission in these 'at-risk' individuals.